The Behring Sea question embracing the fur sealing industry of the North Pacific Ocean, 1898 [electronic resource] - Venning, R. N. (Robert Norris), b. 1854; Canada. Dept. of Marine and Fisheries. (Ottawa : Govt. Print. Bureau, 1899)
Tables. At head of title: From report of the Department of Marine and Fisheries, 1898. Electronic reproduction. Mode of access: Internet. 44